Behavioral treatment of spitting in a child with autism spectrum disorder: Functional analysis, intervention evaluation, and maintenance assessment. (19th August 2020) - Hartz, Renee M.; Luiselli, James K.; Harper, Jill M.
Abstract : Spitting is a socially and hygienically unappealing behavior displayed by some persons who have intellectual and developmental disabilities. In the present study, we conducted a test‐only functional analysis, intervention evaluation, and maintenance assessment with a 12‐year‐old child who had autism spectrum disorder (ASD) and displayed spitting among staff and peers in a special education classroom. Based on hypothesized automatic reinforcement of spitting, intervention combining differential reinforcement and nonexclusionary time‐out was evaluated in an A‐B‐A‐B reversal design. Intervention reduced and eliminated spitting with effects maintained several months after the study. Results support use of nonmatched (social) stimuli in treating automatically reinforced problem behavior and compared to previous research on spitting, the study featured intervention that was informed through functional analysis, implemented beyond brief simulated sessions, and associated with extended response maintenance.